2021
DOI: 10.1002/er.6454
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the supercapacitor performance of flexible MXene /carbon cloth electrodes by oxygen plasma and chemistry modification

Abstract: All-solid-state flexible supercapacitors (FSCs) are promising energy-storage devices in wearable smart electronics. Carbon cloth (CC) has emerged as an ideal candidate as it can fulfill all the required properties for conductive, corrosion-resistant, and lightweight FSC substrates. However, commercial CC is difficult to adhere to without crosslinkers and binders owing to the hydrophobic surface. Herein, oxygen plasma and chemistry methods are selected for hydrophilic modification of commercial CC. Then, Ti 3 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Such a phenomenon can also be observed in other flexible supercapacitors with Ti 3 C 2 T x electrodes and a PVA-based polymer gel electrolyte. 63,64 The capacitance retention was retained at 97% after 5000 cycles and 76% after 10000 cycles, which is comparable to that of a Ti 3 C 2 T x -based flexible supercapacitor. 60,65 A sharp decrease between 8000 and 10 000 cycles may be ascribed to the delamination between the gold foil current collector and the Ti 3 C 2 T x electrodes, which was caused by the dehydrationinduced shrinkage of the polymer electrolyte layer during the long-term running.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…Such a phenomenon can also be observed in other flexible supercapacitors with Ti 3 C 2 T x electrodes and a PVA-based polymer gel electrolyte. 63,64 The capacitance retention was retained at 97% after 5000 cycles and 76% after 10000 cycles, which is comparable to that of a Ti 3 C 2 T x -based flexible supercapacitor. 60,65 A sharp decrease between 8000 and 10 000 cycles may be ascribed to the delamination between the gold foil current collector and the Ti 3 C 2 T x electrodes, which was caused by the dehydrationinduced shrinkage of the polymer electrolyte layer during the long-term running.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…It is also noticed that, compared with the pristine MXene, the P-MXene/C polymer -A electrodes exhibit decreases in the peak at ∼3420 cm –1 that is assigned to the −OH stretching vibration, indicating the reduction of −OH group in the P-MXene/C polymer -A. The −OH group on the MXene surface is normally considered to have little contribution to the pseudocapacitance, , and some theoretical studies have reported that the larger −OH group on the MXene surface may pose a barrier to the ion transfer process and be undesirable for ion storage. , The reduction in the −OH of the P-MXene/C polymer -A electrodes could be conducive to the enhancement of their capacitances.…”
Section: Resultsmentioning
confidence: 99%
“…122 Recently, carbon cloth (CC) was modified using MXene without crosslinkers and binders. 123 This CC/ Ti 3 C 2 T x electrode, when used as a flexible SC, under different bending angles, pursued CV curves only with slight changes. These results suggested that the CC/Ti 3 C 2 T x electrode can fulfill the demand for wearable energy storage devices.…”
Section: Supercapacitors (Scs)mentioning
confidence: 88%
“…These results suggested that the CC/Ti 3 C 2 T x electrode can fulfill the demand for wearable energy storage devices. 123 For on-chip and wearable electronics, micro-supercapacitors (MSCs) are of great interest. 124 Using Ti 3 C 2 T x and reduced graphene oxide (rGO), Couly et al fabricated an asymmetric flexible MSC.…”
Section: Supercapacitors (Scs)mentioning
confidence: 99%